Comparison of Canal Transportation by Two Rotary Systems, Neoniti vs. Wave One, Both Used with Reciprocal Motion - Mohsen Aminsobhani; Arvin Rezaei Avval; Fatemeh Hamidzadeh (Frontiers in Dentistry)
Objectives: Preserving the original canal morphology is the ideal goal during root canal preparation. This study aimed to compare canal transportation at various cross-sections using the Neoniti and Wave One Gold rotary systems, both applied with reciprocal motion.